Noble gas constraints on the fate of arsenic in groundwater. (1st May 2022) - Lightfoot, Alexandra K.; Brennwald, Matthias S.; Prommer, Henning; Stopelli, Emiliano; Berg, Michael; Glodowska, Martyna; Schneider, Magnus; Kipfer, Rolf
Highlights: Noble gases provide insights into CH 4 gaseous phases formed in As contaminated aquifers. CH 4 gaseous phases are disruptive for groundwater (flow) and reduce water renewal. Explanation for As heterogeneity in aquifers with high gas production. As and noble gases are indirectly linked through the in-situ production of CH 4 . Graphical abstract: Abstract: Groundwater contamination of geogenic arsenic (As) remains a global health threat, particularly in south-east Asia. The prominent correlation often observed between high As concentrations and methane ( CH 4 ) stimulated the analysis of the gas dynamics in an As contaminated aquifer, whereby noble and reactive gases were analysed. Results show a progressive depletion of atmospheric gases (Ar, Kr and N 2 ) alongside highly increasing CH 4, implying that a free gas phase comprised mainly of CH 4 is formed within the aquifer. In contrast, Helium (He) concentrations are high within the CH 4 (gas) producing zone, suggesting longer (groundwater) residence times. We hypothesized that the observed free ( CH 4 ) gas phase severely detracts local groundwater (flow) and significantly reduces water renewal within the gas producing zone. Results are in-line with this hypothesis, however, a second hypothesis has been developed, which focuses on the potential transport of He from an adjacent aquitard into the ( CH 4 ) gas producing zone. This second hypothesis was formulated as it resolves the particularly high He concentrations observed, and since external solute input from the overlying heterogeneous aquitard cannot be excluded. The proposed feedback between the gas phase and hydraulics provides a plausible explanation of the anti-intuitive correlation between high As and CH 4, and the spatially highly patchy distribution of dissolved As concentrations in contaminated aquifers. Furthermore, the increased groundwater residence time would allow for the dissolution of more crystalline As-hosting iron(Fe)-oxide phases in conjunction with the formation of more stable secondary Fe minerals in the hydraulically-slowed (i.e., gas producing) zone; a subject which calls for further investigation.